Pertanggungjawaban Pidana Aparat Penegak Hukum dalam Kasus Salah Tangkap Ditinjau dari Perspektif Keadilan Restoratif - Akhiruddin Tanjung; Isfandir Hutasoit; Edwar Kelvin (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to analyze the forms of criminal liability for law enforcement officers in cases of wrongful arrest, viewed through the lens of restorative justice. A wrongful arrest constitutes a procedural violation in law enforcement that not only causes material and non-material harm to the victim but also potentially erodes public trust in law enforcement institutions. This research employs a normative legal research method utilizing conceptual and statutory approaches. Legal materials were gathered through a literature review of legislation, legal doctrine, and various writings concerning restorative justice and the liability of law enforcement officers. Data analysis was conducted qualitatively using a deductive approach. The findings indicate that law enforcement officers who commit procedural errors resulting in a wrongful arrest can be held criminally liable under positive criminal law provisions, such as Article 333 of the Criminal Code (KUHP) regarding the unlawful deprivation of liberty and Article 421 of the KUHP regarding the abuse of authority by an official to compel someone to perform, refrain from performing, or tolerate an act. Furthermore, if the action involves violence or human rights violations, the officers may also be held liable under other relevant criminal provisions. From a restorative justice perspective, resolving wrongful arrest cases is not solely oriented toward punishing the perpetrator but also emphasizes restoring the victim's rights through the rehabilitation of their reputation, the provision of compensation or restitution, institutional apologies, and the restoration of the victim's psychological and social well-being. This approach broadens the criminal justice system's orientation from mere punishment to the reparation of harm suffered by the victim and the strengthening of law enforcement accountability, thereby fostering a criminal justice system that is more humane, equitable, and focused on the protection of human rights.